Globalization and wage polarization - Cozzi, Guido; Impullitti, Giammario (Massachusetts Institute of Technology Press, 2015)
In the 1980s and 1990s, the US labour market experiences a remarkable polarization along with fast technological catch-up, as Europe and Japan improve their global innovation performance. Is foreign technological convergence an important source of wage polarization? To answer this question, we build a multi-country Schumpeterian growth model with heterogeneous workers, endogenous skill formation and occupational choice. We show that convergence produces polarization through business stealing and increasing competition in global innovation races. Quantitative analysis shows that these channels can be important sources of US polarization. Moreover, the model delivers predictions on the US wealth-income ratio consistent with empirical evidence.